Mutations in the p53 Gene in Colorectal Cancer - Hevi Horiza; Iwan Iskandar; Mutia Yuhesti (Alliance oh Health Activists (AloHA), 2024)
Colorectal cancer is the second leading cause of death, which can be caused by diet, lifestyle, the presence of genes that play a role in the cell cycle and its relationship to the cancer growth process, such as groups that trigger tumors (tumor oncogenes) such as race genes and tumor suppressor such as the p53 gene. One of the causes of colorectal cancer is mutation and allelic loss of the p53 gene. Mutations in the p53 gene mostly occur in conserved areas, namely in the exon 5-9 region, and there are also found in areas outside the exon 5-9 region. Efforts to treat and prevent colorectal cancer are chemotherapy and improving diet by consuming fiber-rich foods. Keywords: colon; colorectal cancer; p53 gene mutation; treatment